2016 International Conference on Interactive Technologies and Games (ITAG) 2016
DOI: 10.1109/itag.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Support Dementia: Using Wearable Assistive Technology and Analysing Real-Time Data

Abstract: Support provided to sufferers of Dementia by the National Health Service (NHS) is mainly in the form of personal attendants such as nurses and social workers. The main focus of this paper is to present how the use of assistive technologies can help early sufferers of Dementia patients to overcome barriers in achieving their daily activities and to illustrate how data analytics, such as Complex Event Processing (CEP) in real-time can allow better monitoring of these patients. This activity will contribute to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Complex event processing is a method of tracking and analyzing streams of data surrounding events or anomalies and basing a conclusion from them [227]. It was found that 63 documents are related to this processing technique with applications such as supply chain [228][229][230] and health care [231,232]. Apache Hadoop (or Hadoop) is a software framework used for distributed storage and big data processing using the MapReduce programming model [233], appearing with 42 documents and applications including smart cities [234][235][236], and Social Internet of Things [237].…”
Section: Software Processing Techniquesmentioning
confidence: 99%
“…Complex event processing is a method of tracking and analyzing streams of data surrounding events or anomalies and basing a conclusion from them [227]. It was found that 63 documents are related to this processing technique with applications such as supply chain [228][229][230] and health care [231,232]. Apache Hadoop (or Hadoop) is a software framework used for distributed storage and big data processing using the MapReduce programming model [233], appearing with 42 documents and applications including smart cities [234][235][236], and Social Internet of Things [237].…”
Section: Software Processing Techniquesmentioning
confidence: 99%